Pendampingan Pengisian SPT Tahunan Orang Pribadi Melalui E-Filing di Wilayah Sidoarjo Barat - Fahreza Eka Faradisha; Istiqomah Maulida Multazam; Achmad Wicaksono (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
In this digital era, the process of reporting the Annual Tax Return (SPT) for Individuals can be done online. However, there are still many Taxpayers who experience difficulties related to the procedure for reporting Annual SPT online. Community service activities in the form of assistance in reporting Individual SPT through e-Filing carried out by students of Nahdlatul Ulama University Sidoarjo as part of the Tax Volunteers held by the Directorate General of Taxes (DJP) located at the West Sidoarjo Pratama Tax Service Office. This activity aims to help reduce the spike in taxpayers who will report annual SPTs and optimize the role of Tax Volunteers in assisting Taxpayers. The method used is assistance and service to Taxpayers. As a result, a number of annual SPTs were successfully reported online. It is hoped that this Tax Volunteer activity will be routine every year with a wider coverage area.